Sen on Open and Closed Impartiality - Elmore, Benjamin (Theoria (Pietermaritzburg), 2025)
In this article, I will rebut Amartya Sen's arguments that John Rawls's political philosophy gives us a form of closed rather than open impartiality. I will argue that there is plenty of room within Rawls's own theory of justice to accommodate the requirements of open impartiality. I will appeal to the way the original position is used in public reason and the method of reflective equilibrium to defend Rawls. Given the way that it fits into Rawls's broader theory, the original position should not be construed as a form of closed impartiality, doomed to be infected unduly by parochial cultural values. Rawls's contractualism is more defensible and versatile than Sen envisions. Some elements of Sen's argument have been briefly addressed before, but this article provides the only sustained, systematic treatment of this important issue.